Precision N-Glycoproteomic Profiling of Murine Peritoneal Macrophages After Different Stimulations - Yang, Lujie; Gong, Tianqi; Shen, Huali; Pei, Jiangnan; Zhang, Lei; Zhang, Quanqing; Huang, Yuanyu; Hu, Zuojian; Pan, Ziyue; Yang, Pengyuan; Lin, Ling; Yu, Hongxiu (Frontiers in Immunology, 2021)
Macrophages are important immune cells that participate in both innate and adaptive immune responses, such as phagocytosis, recognition of molecular patterns, and activation of the immune response. In this study, murine peritoneal macrophages were isolated and then activated by LPS, HSV and VSV. Integrative proteomic and precision N-glycoproteomic profiling were conducted to assess the underlying macrophage activation. We identified a total of 587 glycoproteins, including 1239 glycopeptides, 526 monosaccharide components, and 8236 intact glycopeptides in glycoproteomics, as well as a total of 4496 proteins identified in proteomic analysis. These glycoproteins are widely involved in important biological processes, such as antigen presentation, cytokine production and glycosylation progression. Under the stimulation of the different pathogens, glycoproteins showed a dramatic change. We found that receptors in the Toll-like receptor pathway, such as Tlr2 and CD14, were increased under LPS and HSV stimulation. Glycosylation of those proteins was proven to influence their subcellular locations.